Geochemical characteristics of sediment- and mafic rock-hosted Cu deposits in the Kåfjord area, Alta-Kvænangen Tectonic Window, Northern Norway - Simonsen, Sondre Stenvold (UiT Norges arktiske universitet, 2021)
The Precambrian Alta-Kvænangen Tectonic Window (AKTW) located in the northern part of Norway, hosts different types of copper mineralization. Some of Cu occurrences have been previously mined, but their geochemical and stable isotope characteristics have not been a subject of detailed investigations, and therefore the relevant ore-forming processes are still poorly understood. This study, brings new mineralogical, geochemical and stable isotope data collected from the sediment-hosted and the mafic rock-hosted Cu mineralization in the Kåfjord area of AKTW. The Kåfjord area hosts Cu occurrences in sedimentary rocks of the Storviknes formation and in mafic rocks of the Kvenvik formation. Both formations are regionally folded, with Storviknes formation lying stratigraphically above Kvenvik formation. The Cu mineralization is mostly related to epigenetic quartz-carbonate veins. Considering their mineral assemblages and spatial relationship with the host rocks, the veins were subdivided into 5 different types. In the three types of sediment-hosted Cu mineralization, Cu occurs in digenite, bornite and/or chalcopyrite. In contrast, in mafic rock-hosted Cu mineralization, chalcopyrite is the only Cu-bearing mineral. In addition to the epigenetic mineralization, a syngenetic mafic rock-hosted VMS mineralization has also been identified. The mafic rock-hosted quartz-carbonate veins show positive δ13C values, indicating influences from 13C-rich carbonate layers formed during the Lomagundi-Jatuli Event, while the δ13C and δ18O values of the sediment-hosted rocks shows a marine origin. The δ34S values of sulfides from mafic rock-hosted veins indicate an influence of evaporites. The fluid inclusion study revealed that the ore-forming fluid was highly saline with a low to moderate temperature. The high salinity controlled the capability of the fluid to transport Cu in the form of chloride complexes. The same type of highly saline fluid inclusions has been found in the sediment- and mafic rock-hosted Cu mineralization, ...